Olive oil enema in a pre‐term infant with milk curd syndrome. Issue 4 (5th August 2013) - Watanabe, Toshihiko; Takahashi, Masataka; Amari, Shoichiro; Ohno, Michinobu; Sato, Kaori; Tanaka, Hideaki; Miyasaka, Mikiko; Fuchimoto, Yasushi; Ito, Yushi; Kanamori, Yutaka
Abstract: Milk curd syndrome was first reported in the 1960s, but was gradually forgotten because of its low incidence thereafter. This condition in pre‐term infants has been reported over the last decade and has again attracted neonatologists' attention. The present report describes a pre‐term infant with milk curd syndrome. Abdominal distension was evident 14 days after the start of feeding with fortified expressed milk. Abdominal X‐ray showed multiple intraluminal masses surrounded by a halo of air, and ultrasound indicated hyperechoic masses. Along with that history and the appearance of fecal impaction, the diagnosis of milk curd syndrome was confirmed. This baby was treated with olive oil enemas and successive colonic lavage for 3 days, and the symptoms were relieved. Olive oil enema, which softens hard stools and induces smooth movement of these stools, may be an effective and safe first‐line treatment in pre‐term infants with milk curd syndrome.